Diversity of Annelida Worm as a Bioindicator of Water Quality in Unus Estuary, Mataram Lombok - Husnayati Hartini (Jurnal Biologi Tropis, 2022)
Condition of river is strongly influenced by the characteristics and the surrounding environment. Unus River is one of the rivers in Mataram City that flows throughout the year. The flow of the Unus River is used by residents for irrigation purposes, household waste disposal, market waste, industrial waste and so on. The purpose of this study was to determine annelida diversity index and to determine chemical and physical conditions of waters. The study was conducted by dividing into 10 stations by stratified random sampling. Physical and chemical parameters measured were pH, temperature, DO, BOD, C Organic, depth and turbidity. Data analysis is descriptively. The results showed that 6 species found in the estuary of Unus such as Tubifex sp, Branchiura sp, Nereis sp, Lumbriculus sp, Capitella sp and Halobdella sp. Ecosystem conditions are not balanced and there is a tendency to high ecological pressure. Physical and chemistry waters quality are still below the quality standard but there is a tendency DO deficit at each station.